Optimal coupling to high-Q whispering gallery modes with a sub-wavelength metallic grating coupler - Zhou, Y. (2018)
Gold grating patterned on the end facet of an optical fiber is able to excite whispering gallery mode (WGM) in a silica microsphere. With a direct pathway of the metal reflection, the coupled WGM is able to superimpose and create an asymmetric Fano resonance. Since multiple resonances are present – the WGM, grating reflection, and a weak Fabry-Perot resonance along the diameter of the sphere – it is difficult to evaluate the power efficiency directly from the measured spectrum. Using temporal coupled-mode theory, a general model is constructed for the end-fire coupling from a grating to a WGM resonator.